Electrophysical methods of separation of metal cations in the moving salts solution; IOP Conference Series: Materials Science and Engineering; Vol. 135 : Issues of Physics and Technology in Science, Industry and Medicine - Gofman V. N. Valery Nikolaevich; Tuksov I. V.; Timchenko S. N. Sergey Nikolaevich; Shamanin I. V. Igor Vladimirovich; Poberezhnikov A. D. Andrey Dmitrievich; Kazaryan M. A. (2016, 2016)
Title screen